Faktor keberhasilan usaha pada UMKM industri sandang dan kulit di Kecamatan Wirobrajan Kota Yogyakarta - Diansari, Rani Eka; Rahmantio, Rendy (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2020)
This study aimed to test the effect of using accounting information and capital on the business success of Micro Small and Medium Enterprises (MSMEs) in the Wirobrajan District, Yogyakarta Regency. The Population in this research is the MSMEs in Yogyakarta Regency. Sample taken there were only registered with the Department of Trade Industry and Cooperatives on Yogyakarta Regency, MSMEs in the clothing and leather industry, operating for more than five years, take notes on business management, the respondents as many as 34. The sampling technique used purposive sampling. The data analysis technique used in this research includes the quality of data consists of the validity and reliability test—the hypothesis consisting of the multiple linear regression analysis. The result indicates that accounting information and capital have a significant impact on business success